The Effect of Water and Salt Stress on Paspalum dilatatum, a Constituent of Pampas Natural Grasslands - Porcelli, Claudia A. (2024)
The effects of the salt stress on plant growth are usually increased by the water stress. We studied the impact of both stresses in simultaneous pulses of drought and salinity on Paspalum dilatatum. This forage species is native to South America, spread in grasslands in many tropical, subtropical, and temperate areas of the world, and very common in grasslands of the Flooding Pampas of Argentina. Mimicking what happens in nature. We compared a pot experiment, a non-stressed control against water stress for a month (midpoint between field capacity and wilting point), and two saline stresses (moderate, 6 d·Sm−1 and strong, 12 d·Sm−1 ), also for a month. Aerial biomass (green leaf; non-leaf green material, and dry material) and roots were harvested, weighed, and analyzed for nitrogen, phosphorus, and cations. The biomass of all components significantly decreased when both stresses were applied. Water plus strong saline stress reduced by half the total biomasses, compared to the control. The proportion of aerial biomass/root biomass ratio as well as aerial green component/dry materials ratio tend to decrease when subjected to both stresses. Nitrogen concentration in plants was not significantly affected, but phosphorus concentration increased in aerial biomass components, from 0.10 to 0.18 mg·kg−1 between the extreme treatments, but did not change in roots. Sodium concentration in plants increased (i.e., in green leave sodium (Na) increased from 0.27 to 2.01 mg·kg−1 between the extreme treatments), whereas other cations either did not change or decreased, affecting the ratios between them. Sodium performance allows us to infer that the Na accumulation of P. dilatatum behaves in an intermediate range, compared to very tolerant to salts or non-salt tolerant species of the Paspalum genus. In agreement, when salts were applied in the form of a pulse, P. dilatatum tolerated higher salinity than that found by other authors for the same species, using continuous salinity.